Potential involvement of root auxins in drought tolerance by modulating nocturnal and daytime water use in wheat. (28th March 2019) - Sadok, Walid; Schoppach, Rémy
Abstract: Background and Aims: The ability of wheat genotypes to save water by reducing their transpiration rate (TR) at times of the day with high vapour pressure deficit (VPD) has been linked to increasing yields in terminal drought environments. Further, recent evidence shows that reducing nocturnal transpiration (TRN ) could amplify water saving. Previous research indicates that such traits involve a root-based hydraulic limitation, but the contribution of hormones, particularly auxin and abscisic acid (ABA), has not been explored to explain the shoot–root link. In this investigation, based on physiological, genetic and molecular evidence gathered on a mapping population, we hypothesized that root auxin accumulation regulates whole-plant water use during both times of the day. Methods: Eight double-haploid lines were selected from a mapping population descending from two parents with contrasting water-saving strategies and root hydraulic properties. These spanned the entire range of slopes of TR responses to VPD and TRN encountered in the population. We examined daytime/night-time auxin and ABA contents in the roots and the leaves in relation to hydraulic traits that included whole-plant TR, plant hydraulic conductance ( K Plant ), slopes of TR responses to VPD and leaf-level anatomical traits. Key Results: Root auxin levels were consistently genotype-dependent in this group irrespective of experiments and times of the day. Daytime root auxin concentrations were found to be strongly and negatively correlated with daytime TR, K Plant and the slope of TR response to VPD. Night-time root auxin levels significantly and negatively correlated with TRN . In addition, daytime and night-time leaf auxin and ABA concentrations did not correlate with any of the examined traits. Conclusions: The above results indicate that accumulation of auxin in the root system reduces daytime and night-time water use and modulates plant hydraulic properties to enable the expression of water-saving traits that have been associated with enhanced yields under drought.